Participatory research methods and gender data base Bangladesh country paper - Mahbub, Amina (BRAC Research and Evaluation Division (RED), 2020)
Application of Participatory Rural Appraisal (PRA) in rural development as well as in agricultural sectors is quite recent in Bangladesh and most of the PRAs are conducted by NGOs. The review of participatory researches explicitly shows that majority of them were conducted to date for evaluating current status and future potentials of different programs. Few researches were done to explore the baseline situation of the villages. However, the creation of a gender sensitive database based on participatory process is required to assist in the development of gender sensitive technical programs for rural development. In this regard, some measures can be taken to increase women's participation in the participatory process. Yet, for gender sensitive development planning to improve the value of participatory research, the analysis should be done individually along with data collection from men and women's group separately. Community involvement with the overall process of data collection to analysis is considered an effective way in this regard. In this context, Participatory Assessment, Analysis and Action (P AAA) is useful approach to development planning and implementation. It involves all stakeholders from the community people to Thana level officials in a participatory process of assessing, analyzing, and acting on multifaceted problems of rural development.